Maternal fat intake in pregnancy and risk of depressive symptoms in Japanese adolescents: the Kyushu Okinawa Maternal and Child Health Study - Miyake, Yoshihiro; Tanaka, Keiko; Okubo, Hitomi; Sasaki, Satoshi; Arakawa, Masashi (International Journal of Food Sciences and Nutrition, 2024)
The current prebirth cohort study investigated the association between maternal intake of specific types of fatty acids during pregnancy and adolescent depressive symptoms based on the Center for Epidemiologic Studies Depression Scale. Subjects were 873 mother-child pairs. Dietary intake during the preceding month was assessed using a self-administered diet history questionnaire. The risk of depressive symptoms was 23.3% among the 873 adolescents at 13 years of age. Higher maternal saturated fatty acid intake during pregnancy was independently associated with a reduced risk of depressive symptoms in adolescents. Maternal intake of total fat, monounsaturated fatty acids, n-3 polyunsaturated fatty acids, α-linolenic acid, eicosapentaenoic acid, docosahexaenoic acid, n-6 polyunsaturated fatty acids, linoleic acid, arachidonic acid and cholesterol during pregnancy was not significantly related to depressive symptoms in adolescents. Higher maternal intake of saturated fatty acids during pregnancy may be inversely associated with adolescent depressive symptoms.